Medical cannabinoids for painful symptoms in patients with severe dementia: a randomized, double-blind cross-over placebo-controlled trial protocol - Bianchi, Federica; Pautex, Sophie; Wampfler, James; Curtin, François; Daali, Youssef; Desmeules, Jules Alexandre; Broers, Barbara (Frontiers in Pain Research, 2023)
Background: In an observational study in Geneva (Switzerland), we found that administering a standardized THC/CBD oil was feasible, safe, and beneficial in an elderly polymedicated population with severe dementia, behavioral troubles, and pain. Those findings need to be confirmed in a randomized clinical trial. Objectives: The MedCanDem trial is a randomized, double-blind cross-over placebo-controlled trial to study the efficacy of cannabinoids in improving painful symptoms during severe dementia disorders in patients living in long-term care facilities in Geneva. This manuscript describes the MedCanDem trial protocol. Materials and methods: Participants will be patients suffering from severe dementia associated with pain and behavioral troubles and living in long-term care facilities. We selected five facilities specialized in caring for severely demented patients in Geneva (Switzerland). A total of 24 subjects will be randomized 1:1 to the sequence study intervention/placebo or the sequence placebo/study intervention. Patients will receive study intervention treatment or placebo for eight weeks, and then after a one-week wash-out, treatments will be inversed for another eight weeks. The intervention will be a standardized THC/CBD 1:2 oil extract, and the placebo will be a hemp seed oil. The primary outcome is the reduction from the baseline of the Cohen-Mansfield score; secondary outcomes include the reduction in the Doloplus scale, the reduction of rigidity, the monitoring of concomitant drugs prescription and de-prescription, the safety assessment, and a pharmacokinetic evaluation. The primary and secondary outcomes will be assessed at the baseline, after 28 days, and at the end of both study periods. In addition, safety laboratory analysis, pharmacokinetic evaluation, and therapeutic drug monitoring for the cannabinoids will be evaluated through a blood sample analysis conducted at the beginning and the end of both study periods. Discussion and conclusion: This study will allow us to confirm the clinical results observed during the observational study. It represents one of the few studies aiming to prove natural medical cannabis efficacy in a population of non-communicating patients with severe dementia, experimenting with behavioral troubles, pain, and rigidity. Trial registration: The trial has Swissethics authorization (BASEC 2022-00999), and it is registered on clinicaltrials.gov (NCT05432206) and the SNCTP (000005168).